The explanationist argument for moral realism - Sinclair, Neil (University of Calgary Press, 2011)
In this paper I argue that the explanationist argument in favour of moral realism fails. According to this argument, the ability of putative moral properties to feature in good explanations provides strong evidence for, or entails, the metaphysical claims of moral realism. Some have rejected this argument by denying that moral explanations are ever good explanations. My criticism is different. I argue that even if we accept that moral explanations are (sometimes) good explanations the metaphysical claims of realism do not follow.